New gold dental alloy for metal-ceramic restorations - Rudolf Rebeka; Kramberger Janez; Zupančič-Hartner Tjaša; Marić-Dragaš Aleksandra; Lazić Vojkan (Serbian Medical Society - Dental Section, Belgrade, 2006)
Introduction: Porcelain to metal fused alloys with Au content are most frequently used in dentistry. Their characteristic is high biocompatibility and well fusion to ceramics. Aim of the study: The aim of this study was to present the procedure of production and technology of developing the new dental alloy with high gold content (Au). Materials and Methods: The dental alloy was melted and cast in a vacuum-induction melting furnace. Casting was followed by subsequent thermo-mechanical treatments (the procedures of profile and polish milling, and thermal treatment) and the cutting strips into regular shapes. Testing of the new Au dental alloy included an examination of alloy's final condition. The measurement of hardness was carried out according to standard 6507-1:1998, and static tensile testing was performed for determination of the mechanical properties. Microscopic analysis of the dental alloy and the finished metal-ceramic bridge included an observation of the polished surface, and by performing qualitative and quantitative micro-chemical analyses. Results: The mechanical properties and hardness of new dental gold alloy was: Rp0.=630 [N/mm2], Rm =710 [N/mm2], A= 9%, 170 HV and CTE (25-600°C) about 14,55×10-6K-1. Macro-inspection of the finished metalceramic bridge showed that there was no porosity. However, during scanning electron microscopic examination, one of the tested sample shows porosity in one alloy region and in the ceramic layer. Detailed examination of the ceramic layer's surface showed that there were two types of air or gas bubbles - larger with distinct bubbles (type I) and smaller with clearly porous microstructure (type II). Conclusions: According to the results of this study, it can be concluded that this new dental alloy from Zlatarna Celje satisfied all the required standards regarding mechanical properties and hardness. The application of new dental alloy with high gold content depends on the adequate technology when firing ceramics. It is necessary to obtain accurate oxidation temperature and cooling rates of metal-ceramic restorations because, otherwise, different defects may appear.